Morphological and anatomical studies of the seeds and seedlings of Eucalyptus pilularis and E. umbra - Beltrati, Celia Massa (1981)
Morphological and anatomical aspects of seeds and seedlings of Eucalyptus pilularis Sm. and E. umbra R.T. Baker were studied in detail and found to be similar, with the exception of some anatomical features of the testa and the average length of the fertile seeds, which is significantly different for the two species.